Transformation of Writing Habit on Students at Junior High School and Vocational High School Awal Karya Pembangunan Lubuk Pakam - Dian Marisha Putri; Liza Amalia Putri; Rahmadsyah Rangkuti (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Writing Learning must still be based on Core Competencies (KI) which are then announced in Basic Competencies (KD) and Indicators through learning material. Similarly, the writing material results from field observations and observations. Add another competition for scientific publication of adolescents conducted at the District / City, Provincial and National Level. While the material can be achieved and competitions can be followed. In this paper, it is discussed giving habit transformation of writing through concepts and for example making students see general writing, then students look for references and field data. Only to discuss the substance of scientific writing needs field reinforcement data carried out by students and must be guided directly by the guidance teacher through habit transformation of writing so that the validity and writing of scientific writings can be accounted for. The results of habit transformation in adolescent students are quite significant, so that the 5 texts that have begun to be seen develop and several texts in the process of improvement. Of the seven texts prepared the results are quite encouraging. 2 manuscripts have started the results of their writings by fulfilling the rule of writing.